Estudio socioeconómico de propietarios de tiendas de abarrotes en la parroquia Aurora, cantón Daule, provincia del Guayas - Chávez Arismendi, Erika Paulina (2024)
The objective of this paper is to analyze the socioeconomic situation of grocery store owners in the Aurora Sector, Daule canton, Guayas province, in order to understand the little studied reality. For this, the theoretical foundations on the characteristics for the socioeconomic study are developed; an analysis of the behavior of these enterprises is made. The results of this research were obtained through a mixed approach methodology (quantitative-qualitative), the scope of the research is descriptive using techniques and instruments such as observation, survey and interview; the type of sampling applied is nonprobabilistic by convenience. The survey was conducted with 30 grocery store owners in the downtown sector of La Aurora. It was concluded that the economic situation of the grocery store owners depends on the number of people in their establishments.